The knowledge of the artisanal fishermen from Macaé (RJ): subsidies for the conservation and management of the marine fishery resources - Evelyn Raposo da Silva; Luciano Gomes Fischer; Michael Maia Mincarone (Boletim do Observatório Ambiental Alberto Ribeiro Lamego, 2017)
The present study evaluated local traditional knowledge and cataloged the main species of marine fish of commercial interest in Macaé. Fishes were identified both scientifically and ethnotaxonomically. We identified 131 species corresponding to both 81 popular monomial names and 66 binomial names. The results showed that the main criterion for fish classification is based on the morphological characteristics, however criteria such as ontogeny and habitat are also used. The study concluded that local knowledge is an important source of information and should be considered in the process of formulating effective management and conservation strategies of fishery resources.